Comparison of pedicled versus free flaps for reconstruction of extensive deep sternal wound defects following cardiac surgery: A retrospective study. Issue 4 (29th March 2021) - Falkner, Florian; Thomas, Benjamin; Haug, Valentin; Nagel, Sarah S.; Vollbach, Felix H.; Kneser, Ulrich; Bigdeli, Amir K.
Abstract: Background: Myocutaneous pedicled flaps are the method of choice for sternal reconstruction after deep sternal wound infection (DSWI) following cardiac surgery. We set out to investigate whether free flaps provide a superior alternative for particularly extended sternal defects. Methods: Between October 2008 and February 2020, 86 patients with DSWI underwent sternal reconstruction with myocutaneous flaps at our institution. Patients were retrospectively grouped into pedicled (A; n = 42) and free flaps (B, n = 44). The objective was to compare operative details, outcome variables, surgical as well as medical complication rates between both groups, retrospectively. Binary logistic regression analysis was applied to determine the effect of increasing defect size on flap necrosis. Results: Rates of partial flap necrosis (>5% of the skin island) were significant higher in pedicled flaps ( n = 14), when compared to free flaps ( n = 4) (OR: 5.0; 33 vs. 9%; p = .008). Increasing defect size was a significant risk factor for the incidence of partial flap necrosis of pedicled flaps ( p = .012), resulting in a significant higher rate of additional surgeries ( p = .036). Binary regression model revealed that the relative likelihood of pedicled flap necrosis increased by 2.7% with every extra square‐centimeter of defect size. Conclusion: To avoid an increased risk of partial flap necrosis, free flaps expand the limits of extensive sternal defect reconstruction with encouragingly low complication rates and proved to be a superior alternative to pedicled flaps in selected patients.